2017
DOI: 10.3171/2016.1.jns151842
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Simpson grading system and recurrence-free survival after surgery for World Health Organization Grade I meningioma

Abstract: OBJECTIVE The clinical significance of the Simpson system for grading the extent of meningioma resection and its role as a predictor of the recurrence of World Health Organization (WHO) Grade I meningiomas have been questioned in the past, echoing changes in meningioma surgery over the years. The authors reviewed their experience in resecting WHO Grade I meningiomas and assessed the association between extent of resection, as evaluated using the Simpson classification, and recurrence-free survival (RFS) of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 37 publications
8
98
1
3
Order By: Relevance
“…In addition, WHO grade I meningioma have good prognosis after gross total resection. The recurrence rates of WHO Grade I convexity meningiomas are quite small (0.4%) after complete resection [15]. Our study also demonstrated good prognosis of angiomatous meningioma after gross total resection.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, WHO grade I meningioma have good prognosis after gross total resection. The recurrence rates of WHO Grade I convexity meningiomas are quite small (0.4%) after complete resection [15]. Our study also demonstrated good prognosis of angiomatous meningioma after gross total resection.…”
Section: Discussionsupporting
confidence: 69%
“…Since angiomatous meningioma belongs to this group, it has a similar behavior. In a recent study, overall tumor recurrence rates of WHO grade I meningioma for Simpson resection Grades I, II, III, and IV were 5%, 22%, 31%, and 35%, respectively [15]. In addition, WHO grade I meningioma have good prognosis after gross total resection.…”
Section: Discussionmentioning
confidence: 99%
“…10 Of gliomas and meningiomas, which are the major subgroup, the gliomas are more common in males and meningiomas are more common in females. 19,27 The white (Caucasian) race has been shown to be at moderate-to-high risk for gliomas, although a similar association is not evident for meningiomas. Based on tumor occurrence, a similar pattern is expected in the incidence of hydrocephalus in these patients.…”
Section: Tumorsmentioning
confidence: 98%
“…Survival times are known to be prolonged if GTR is achieved in patients with glioblastoma. 7,8 In human patients with meningioma, GTR resulted in a decrease in the rate of recurrence 29 and prolonged survival. 30 The intraoperative use of FS may assist in the resection of homogeneously stained brain tumors in dogs, leading to improved rates of GTR and, hence, long-term survival; however, additional studies are required to confirm this.…”
Section: Discussionmentioning
confidence: 99%